A pilot study on the Spanish version of the Psychosocial Adjustment to Illness Scale (PAIS‐SR) with carers of people with Parkinson's disease - Mari Carmen Portillo; Leire Ambrosio; Raquel Lanas Martín; Maria Victoria Navarta; MEugenia Ursua Sesma; Mario Riverol Fernández (Wiley, 2019)
Abstract Aim To report the cross‐cultural adaptation and pilot study of the ongoing validation of the Spanish version of the Psychosocial Adjustment to Illness Scale with carers of people with Parkinson's disease. Design Cross‐cultural adaptation and pilot study with a cross‐sectional validation design of the Spanish version of the Psychosocial Adjustment to Illness Scale - Carers. Methods Twenty‐one carers of people with Parkinson's disease from a Primary Care practice in Spain were recruited and completed the PAIS‐Carers, the SF‐36 Health Survey, the Brief COPE Inventory and an assessment form. SPSS 23.0 was used to determine viability/acceptability and preliminary aspects of internal consistency of the instrument. Results Five of the seven domains presented floor effect (71.42%), and only one presented ceiling effect (14.28%). The internal consistency of the scale and domains showed acceptable values (over 0.7). The content validity of the Spanish version seemed satisfactory with positive comments in general from participants.